Charting the Rough Journey to 'Home': The Contribution of Qualitative Longitudinal Research to Understandings of Homelessness in Austerity. Issue 4 (27th October 2021) - Davidson, Emma; Nugent, Briege; Johnsen, Sarah
Abstract : This article reflects on the contribution of qualitative longitudinal research (QLR) to understandings of homeless peoples' experiences of support service interventions in an era of austerity in the UK. It brings into 'analytic conversation' data from qualitative longitudinal evaluations of homeless support projects operated by voluntary sector organisations in Scotland. With fieldwork spanning 2014-2019, the analysis expands the analytical potential of pooling small-scale studies through an interrogation of individuals' 'journeys' through homelessness services and their rough path to 'home'. By reflecting on our substantive findings, the article explores the added value and challenges of a longitudinal approach. It concludes that while QLR can deliver deep insight into lives lived by vulnerable populations and potentially reduce the distance between policy makers and those affected, its benefits must be balanced against pragmatism and the ethical responsibilities associated with the method.